PKM Embedded System Pengering Cerdas dan Pengolahan Alkali Treated Cottonii Chips pada Pembudidaya Rumput Laut Karya Bersama Mampie Kabupaten Polman - Andi Rosman N; Ilham Ilham; Baso Ali (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this Community Empowerment Program (PKM) activity is to apply microcontroller-based smart dryer embedded system technology that can help speed up the drying time of seaweed in the Karya Bersama cultivation group. In addition, it also provides new knowledge and skills in terms of post-harvest seaweed management by making processed flour products from cottonii chips. The method of activity implementation consists of observation, post-harvest seaweed management counseling activities, training in making smart dryers, and training in making Cottonii Chips. The results achieved in this PKM activity are (1) the existence of a seaweed smart dryer embedded system; (2) increased knowledge and skills of partners in conducting post-harvest seaweed management. Partners have been able to use the seaweed smart dryer embedded system well and partners have been able to make Cottonii Chips flour.